2010
DOI: 10.5152/tjr.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Depression in Premenopausal Women with Primary Fibromyalgia Syndrome

Abstract: Objective: Sedentary lifestyle, depression and lack of physical activity may lead to a decrease in bone mineral density (BMD) in patients with fibromyalgia syndrome (FMS). The aim of this study was to evaluate the role of FMS in the development of osteoporosis and the impact of depression on the BMD. Materials and Methods: Fifty premenopausal women with a diagnosis of FMS according to the American College of Rheumatology (ACR) criteria and 40 premenopausal healthy controls were included in the study. A structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our present findings are in concordance with previous research in which investigators assessed BMD by QUS at the distal radius that found that FMS was associated with osteopenia and osteoporosis (Babu et al, 2015). Similarly, researchers reported that BMD values at the lumbar spine (Olama et al, 2013;Tander et al, 2010) and femoral neck (Garip Cimen et al, 2015) were significantly lower in patients with FMS than in healthy controls. In a recent systematic review and metaanalysis, authors reported that BMD at the lumbar spine is decreased in patients with FMS compared with healthy individuals and recommended that patients with FMS should be assessed for risk of osteoporosis (Upala et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our present findings are in concordance with previous research in which investigators assessed BMD by QUS at the distal radius that found that FMS was associated with osteopenia and osteoporosis (Babu et al, 2015). Similarly, researchers reported that BMD values at the lumbar spine (Olama et al, 2013;Tander et al, 2010) and femoral neck (Garip Cimen et al, 2015) were significantly lower in patients with FMS than in healthy controls. In a recent systematic review and metaanalysis, authors reported that BMD at the lumbar spine is decreased in patients with FMS compared with healthy individuals and recommended that patients with FMS should be assessed for risk of osteoporosis (Upala et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Because FMS is characterized by chronic widespread pain and tenderness, researchers have also examined the relationships between clinical features, including global pain, TPCs, and disease severity, and bone mass in FMS patients and have, again, reported conflicting results (Babu et al, 2015; Garip Cimen et al, 2015; Jensen et al, 2003; Olama et al, 2013; Tander et al, 2010). Although it is well-known that patients with FMS have decreased pain thresholds (Chinn et al, 2016), and PPT has proven to be a useful measure for evaluating the symptom of tenderness and pressure algometry (Chesterton et al, 2007), to date there has been no evidence of its relationship with bone status in FMS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menopause, aging, deficient calcium and vitamin D intake, smoking, alcohol use, immobility, drugs, hormonal and renal diseases have been suggested for the etiology of OP [4][5][6]. In recent years major depression has been also demonstrated as a risk factor in the development of OP [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%